Quality of information disclosure, property rights, and bank loans: A bank heterogeneity perspective - Xichan Chen; Wanli Li; Shiyang Hu; Xing Liu (China Journal of Accounting Research, 2019)
Using the context of the financial reform and the development of the non-state sector in China in the past decade, we examine the roles that the quality of information disclosure and property rights play in the allocation of different types of bank credit. We find that foreign banks and policy banks exercise "financial discrimination," and that local commercial banks, large state-owned commercial banks, national joint-stock banks, local city commercial banks, and rural commercial banks not only exercise financial discrimination but also provide significant "financial support" to non-state-owned enterprises by providing more lending opportunities and larger loans. However, when enterprises commit information disclosure violations, the local commercial banks, national joint-stock banks, local city commercial banks, and rural commercial banks reverse their credit decisions and begin to exercise financial discrimination against non-state-owned enterprises. At the same time, large state-owned commercial banks continue to provide financial support to non-state-owned enterprises. We also find that the quality of the information disclosed by enterprises has a moderating effect rather than an intermediary effect on the relationship between property rights and bank loans. Overall, the results of this paper shine new light on the market-oriented reform of the banking industry, and provide new empirical evidence for the presence of financial discrimination in the supply of bank credit. Our findings also have practical implications for solving the financing difficulties of non-state-owned enterprises.
Keywords: 650; Bank loans; Property rights; PSM; Quality of information disclosure